Control de ingresos de la gasolinera del Sindicato de Choferes Profesionales Isla de Bejucal en el periodo 2021. - Ruiz Mora, Marcos Paul (2022)
In Ecuador there are 1062 gas stations, 45% of gasoline service stations are in the province of Guayas, Pichincha and Manabí, with the provinces of Galapagos and Orellana having the fewest gas stations, the brands of gas stations such as Terpel Gas Station, PetrolRios Gas Station, and Petro Ecuador Gas Station, but lately brands such as Primax and P&S have gained weight in the Ecuadorian market. Sales are the economic engine of all types of companies and, as is to be expected, without sales, organizations would not generate income that defines their success, for this reason a detailed control of the company must be kept. With the completion of this case study, it is intended and expected to examine the registration of income from sales and other activities in an effective manner in the Gas Station of the Parochial Union of Professional Drivers Isla Bejucal, so that, in this way, the gas station can improve their income and therefore the real state of the organization can be known, for this reason it is that on many occasions some companies have been affected by not knowing how to keep an adequate control of their income. It is necessary to implement instructions that guide the company to have an adequate control that justifies both its income as well as its expenses, in addition to its various activities in the same way, they must all be properly registered, having said this, it can be shown that the control of income It is of the utmost importance and plays a notable role in companies.